The Rejected Versions in Plato's Symposium - Luz, Menahem (PLATO JOURNAL, 2015)
Apollodorus' prelude to Pl. Symp. is a complex rejection of earlier accounts of Socrates' participation in a symposium. This can be examined contextually as a literary mannerism, or sub-textually as a rejection of previous literary versions of this topos. Neither approach contradicts the other, but scholars have found difficulties in finding any earlier author who could have been rejected. Recently, it has been argued that Xen. Symp. preceded Pl. Symp. acting as a catalyst for Plato's work. However, if neither was the first on a sympotic theme in a Socratic dialogue, we need not presume that Apollodorus referred to Xenophon, but rather that both responded to an earlier author. Scholars suggest various candidates although none has been proven. However, one source has not attracted attention: two anecdotes recorded in PFlor 113 where Antisthenes depicts both Socrates and himself as critical of symposia in general. The conclusions of my paper are that the contents of these anecdotes can be seen as the raw kernel out of which both Xenophon and Plato could have responded.